Con: Tolvaptan for autosomal dominant polycystic kidney disease—do we know all the answers?. Issue 1 (11th October 2018) - Gross, Peter; Schirutschke, Holger; Paliege, Alexander
ABSTRACT: According to recent literature, tolvaptan ameliorates the natural decline of renal function in autosomal dominant polycystic kidney disease. Tolvaptan is an orally available vasopressin V2 receptor antagonist. We describe herein the remaining questions and problems: it is unclear from the published work what influence tolvaptan has on total kidney volume. The consequences of hepatotoxicity for the subsequent dosing of tolvaptan have not been reported. A vasopressin V2 antagonist will cause polyuria and polydipsia and tolvaptan may influence quality of life (QOL), however, there are no QOL data. The cost-effectiveness of tolvaptan is borderline. It is unknown at which stage of renal failure tolvaptan therapy may have to be stopped. There are no established criteria to determine the ineffectiveness of tolvaptan. It is presently undecided whether a steady high water intake is able to imitate the renal effects of tolvaptan. Finally, the cause of worsening glomerular filtration rate after the start of tolvaptan is unknown.